#AlternativeArtschool // an interstitial space for creative dissent. Issue 1 (1st April 2017) - Gale, Cathy
The Alternative Art School (AAS) is conceived as an open-ended pedagogic tool through which to interrogate the conditions and consequences of contemporary education. It is interdisciplinary in scope, but focuses on the values of design education, while challenging assumptions of the academic status quo. As a 'school' within a school the AAS exploits the opportunities of art school to envisage alternatives in a staff−student collaboration. Extra-curricular and unmarked, the AAS is framed as a case study here employing a dialogic process that aims to disrupt reductive government policy and challenge the fusion of commerce and culture. In this way students are encouraged to reframe their experiences and ambitions from a more critical position and to inspire change through creative dissent.